2020
DOI: 10.1097/ijg.0000000000001479
|View full text |Cite
|
Sign up to set email alerts
|

A New Technique of iPhone 11 Pro Max Smartphone-aided Angle Video and Standstill Image Documentation

Abstract: In this report, the authors highlight 2 effective and simple techniques of video documentation of the anterior chamber angle using the newer generation iPhone, iPhone 11 Pro Max. In these techniques, we also used a commercially available macro lens with the phone. The patient positions his/her chin on a slit-lamp biomicroscope as done during a routine slit-lamp examination. The first observer places the gonioscope over the patient’s eye and projects a thin slit beam of light of the slit-lamp biomicroscope alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…They used an external light source and the camera function of the smartphone to record intricately detailed images of the mydriasis cataract [25]. Moreover, Pujari A, et al demonstrated a method for photographing the iridocorneal angle using the latest smartphone and external slit-lamp biomicroscope [26]. Finally, Chiong et al invented the three-dimensionally (3D) printed smartphone attachment, which uses the smartphone's light source and camera function [27].…”
Section: Discussionmentioning
confidence: 99%
“…They used an external light source and the camera function of the smartphone to record intricately detailed images of the mydriasis cataract [25]. Moreover, Pujari A, et al demonstrated a method for photographing the iridocorneal angle using the latest smartphone and external slit-lamp biomicroscope [26]. Finally, Chiong et al invented the three-dimensionally (3D) printed smartphone attachment, which uses the smartphone's light source and camera function [27].…”
Section: Discussionmentioning
confidence: 99%
“…The current capability of SI in the observation of anterior segment features is promising. Refined techniques using either gonio or macro lens combinations make it possible to capture high-quality videos and standstill images of the iridocorneal angle ( 422 , 423 ). A trial conducted by Pujari et al found that inferior angle measurements acquired using the iPhone-macro lens combination demonstrate excellent correlation with measurements acquired using AS-OCT ( 424 ).…”
Section: Teleophthalmology and Smartphone Fundus Imagingmentioning
confidence: 99%
“…Previously anterior chamber angle could be imaged only with slit-lampbased gonio-photography, however, recently smartphone-based anterior chamber angle imaging techniques have been described. 5,6 These techniques utilized independent smartphone imaging or placement of an adapter on a smartphone camera which is then used to image the anterior chamber angle via a goniolens devoid of a slit lamp. We have previously reported anterior segment imaging using an intraocular lens (IOL) attached to a smartphone camera called anterior segment photography with an intraocular lens (ASPI), 7 and in this report we extend as well as describe its use to photograph the anterior chamber angle aided with a goniolens which can be used as a cost-effective screening tool.…”
mentioning
confidence: 99%
“…They also performed corneal wedge examination and documentation using the slit beam of a slit lamp as well as that of a direct ophthalmoscope. 6 Their technique, however, required the use of a relatively expensive smartphone. We have utilized an IOL as a magnifying lens attached to a smartphone camera and obtained high resolution, clear, and magnified images of the anterior chamber angle, thereby expanding the use of ASPI for gonio-imaging.…”
mentioning
confidence: 99%
See 1 more Smart Citation